Studi Komparatif pada Pengembangan Potensi Desa Wisata Semen dan Desa Wisata Serang Kabupaten Blitar - Nabilla Syahda Rahmawati; Rachmawati Novaria; Hasan Ismail (PANUNTUN (Jurnal Budaya, Pariwisata, dan Ekonomi Kreatif), 2026)
This study is motivated by differences in tourism village development patterns in Blitar Regency, particularly between Semen Tourism Village, which is based on mountain ecotourism, and Serang Tourism Village, which is based on coastal tourism. These differences indicate variations in the implementation of the 6A concept (Buhalis, 2000), which has not yet been fully integrated within community-based destination management. The aim of this study is to analyze and compare tourism village development based on the six components of 6A, namely attraction, amenities, accessibility, activities, ancillary services, and available package. This research uses a qualitative approach with a descriptive comparative method. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results show that Semen Tourism Village is more focused on ecotourism, educational activities, and integrated nature-based tourism packages, while Serang Tourism Village emphasizes family recreation, cultural events, and coastal attractions. In terms of facilities, accessibility, supporting services, and tourism packages, both villages show different levels of development that complement each other based on local potential. The implementation of the 6A concept in both tourism villages has been carried out, but with different development orientations according to local characteristics. Semen Village tends to be education and ecology oriented, while Serang Village is more focused on recreational and family-based tourism experiences.